Phasing kit - Aidir Jamil (2017)
Phasing Kit is making use of basic electrical component and its characteristics to help us in carrying out especially on high voltage (HV) distribution cable phase identification work such as Red, Yellow and Blue (R, Y, B) phases or with new convention such as Line 1, Line 2 and Line 3 (L1, L2, L3). In present modern world, we often look at very high-tech or sophisticated circuitry designed in an equipment for specific or various applications in our daily life or work, forgetting that individual component itself can be utilized so that to help us achieve certain application or used if we understand their characteristics. This modern circuitry often consists of numerous electrical components and processors which undergoes different stages and processes at any single time. In turn, all these processes will finally give the output to the requirements and specificationsthat are set in the precondition and post condition states. In this report, we will study the basic characteristic of different type of electrical components namely a resistor and a capacitor. Then, making use of its characteristics to assist us in carrying out the work of identifying different phases of distribution cable correctly. We will study individual component behaviors and find out the problem we may face when selecting different rating for each component with the help of certain measuring equipment. After which, we will eventually decide which component and its rating best can be used in enhancing the existing Phasing Kit. As a reminder, this enhance Phasing Kit which I proposed for my FYP requirement is not the commonly known as ‘live’ phasing equipment which are readily available in the market that are used to check the final phasing of the energized cables before they are being connected to the distribution network or put on load. Instead, this Phasing Kit I am trying to enhance is use strictly while the cables are being de-energized and is safe to work on. It is specifically use to identify the core phasing before any cable jointing, connection or termination work. I hope there are no misunderstanding or misconception on the title. If a better name could be proposed, it would be very much help to eliminate the misconception.